Exploring Student Perspectives on Information and Communication Technology - Riolandi Akbar; Lenni Astuti; Arip Widodo (Journal of Innovative and Creativity, 2026)
This study aims to explore students’ perspectives on the role of Information and Communication Technology (ICT) in supporting academic and social activities in higher education. A descriptive qualitative approach was employed using content analysis of academic sources, including journal articles, scholarly books, conference proceedings, and research reports obtained from reputable databases. The findings indicate that students generally perceive ICT positively, particularly in enhancing learning flexibility, access to information, academic collaboration, and learning motivation. Nevertheless, several challenges were identified, including disparities in digital literacy, limited technological infrastructure, digital distraction, and concerns related to students’ well-being and learning balance. In addition, ICT use among students extends beyond academic purposes, functioning as a medium for social interaction and entertainment that may influence learning productivity. These findings suggest the need for inclusive and strategic ICT implementation that emphasizes digital literacy development, pedagogical effectiveness, and student-centered approaches. By incorporating students’ perspectives as primary ICT users, higher education institutions can foster more equitable, effective, and sustainable digital learning environments.